ECOLOGICAL CONCEPTS IN THE STORY OF PURWA LEATHER PUPPET - Djoko Sulaksono; Kundharu Saddhono (Universitas Sebelas Maret, 2017)
The story of purwa leather puppet is replete with ecological and environmental values. The concept of environment or natural state in purwa leather puppet performance is presented by the puppet master in the form of turbulence, janturan, pocapan, and prampogan. Besides being stated by the puppet master, the concept of environment is also found in stories and pictures. The concept of water in the purwa puppet story is found in the play namely Ramayana, Dewa Ruci, Karna Tandhing, Adon-adon Rajamala, and Cupu Manik Astagina.